2008
DOI: 10.1158/0008-5472.can-08-0364
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Ovarian Cancer-Initiating Cells from Primary Human Tumors

Abstract: The objective of this study was to identify and characterize a self-renewing subpopulation of human ovarian tumor cells (ovarian cancer-initiating cells, OCICs) fully capable of serial propagation of their original tumor phenotype in animals.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
1,103
3
9

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,170 publications
(1,163 citation statements)
references
References 58 publications
32
1,103
3
9
Order By: Relevance
“…[5][6][7][8][9] As shown in Figure 1b, all cell lines generated tumorospheres, and flow cytometry analyses showed that CD44 þ CD24 À population was highly enriched in tumorospheres (Supplementary Figure S1A). We sorted CD44 þ CD24 À cells from spheres of prostate and breast cancer using fluorescence-activated cell sorting (FACS) and achieved a purity of 495% as judged by postsorting flow analysis (Figure 1c).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…[5][6][7][8][9] As shown in Figure 1b, all cell lines generated tumorospheres, and flow cytometry analyses showed that CD44 þ CD24 À population was highly enriched in tumorospheres (Supplementary Figure S1A). We sorted CD44 þ CD24 À cells from spheres of prostate and breast cancer using fluorescence-activated cell sorting (FACS) and achieved a purity of 495% as judged by postsorting flow analysis (Figure 1c).…”
Section: Resultsmentioning
confidence: 90%
“…Collectively, our data suggest that both CSCs and spheres exhibited diverse stem cell-associated characteristics, consistent with previous reports. [5][6][7][8][9] CSCs overexpressed BAD with elevated phosphorylation. As CSCs are resistant to drugs 11 and phosphorylated BAD correlates with drug resistance in cancer patients, 25 we determined the level of BAD expression and phosphorylation in CSCs and tumorospheres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether induction of TG2 by TGF-b1 has a role, we measured the effects of TG2 knock-down on spheroid formation. Transduction of short hairpin Prior studies indicated that cancer cells with stem cell phenotype aggregate as spheroids when cultured under low adherence conditions in the absence of differentiating factors (Al-Hajj and Clarke, 2004;Zhang et al, 2008). Further, cancer cells cultured as spheroids are enriched in cells with stem phenotype (Dontu et al, 2003).…”
Section: Tgf-b-regulated Tg2 Expression Is Significant To Emt and Ocmentioning
confidence: 99%
“…OC cells transitioned to a mesenchymal phenotype form spheroids, which allow dissemination in the peritoneal cavity. Spheroids are enriched in CD44 þ /CD117 þ cells, phenotype recognized as a signature for OC initiating cells (OCIC) (Zhang et al, 2008). TG2 knock-down prevented TGF-b-induced EMT, decreased the number of CD44 þ /CD117 þ cells and blocked spheroid formation by OC cells.…”
Section: Introductionmentioning
confidence: 99%